PENGEMBANGAN BAHAN AJAR MEDIA PEMBELAJARAN MATEMATIKA BERBASIS LECTORA INSPIRE DI SEKOLAH DASAR - Ika Rostika; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
This research aims to develop teaching materials for mathematics learning media based on lectora inspire in elementary schools on the material of plane properties, to see the response and understanding of students. The subject of this study was the fifth grade students of SDN Pasir. Amounting to 30 students in the 2018/2019 academic year. Data collection is obtained by tests, questionnaires and documentation. The results of the study were (1) obtained an average score of expert validation of 84.15% with the category "feasible" (2) the average score of student responses with a percentage of 97.6% which was included in the "very good" category ( 3) post-test average score of 81,49% with the "very good" category so that it can be concluded that  the teaching material of lectora inspire-based mathematics learning media is suitable to be used in fifth grade on plane properties and can provide understanding to studentsnin fifth grade plane properties.